Pengaruh WOM, Pelayanan, Harga, Lokasi, dan Promosi Terhadap Keputusan Pembelian UD.Ovimart Jember - Mahara Saputra; Hamzah Fansuri Yusuf; Ahmad Sauqi (CV. ITTC INDONESIA, 2025)
Ovimart is a business operating in the staple goods trade sector, providing essential daily needs for the community, particularly in Jember Regency. This study was conducted to evaluate the influence of Word of Mouth, service quality, price, location, and promotion on consumer purchasing decisions at UD. Ovimart Jember. The research is motivated by the intense competition in the staple goods trade sector, which requires business actors to better understand the factors that influence consumer decisions.A quantitative approach was used in this study, with data collected through questionnaires distributed to consumers who have made at least two purchases. The data were analyzed using multiple linear regression methods. The findings show that Word of Mouth, Price, and Promotion do not have a partial effect on purchasing decisions. However, Service Quality and Location do have a significant effect. Furthermore, all five variables simultaneously influence purchasing decisions. These results provide valuable insights for staple retail businesses in determining appropriate and competitive marketing strategies.